The influences of being acquired on subsidiary innovation adoption - Barden, Jeffrey Q. (Strategic Management Journal, 2012)
Abstract Received research suggests that a firm subsidiary's acquisition by a new owner has countervailing effects on the subsidiary's innovation adoption behavior. On one hand, ownership change can make a subsidiary more receptive to innovation by reducing some inertial forces and introducing new resources to overcome others. Alternatively, the costs and demands of an acquisition can draw decision makers' attention away from important innovations in the technological environment. This event history study disentangles these countervailing influences by examining the influences of radio station ownership change on stations' adoptions of HD Radio ® technology. The study finds that a change in ownership control does have a positive direct influence on the likelihood of technology adoption, but that it also curtails tendency for subsidiaries to subsequently mimic others' technology adoptions. Copyright © 2012 John Wiley & Sons, Ltd.